Unmasking the mimic: when sepsis disguises as dengue shock syndrome - Yadav, Anita; Kamath, Anusha; Gangane, Neha; Choudhary, Amruta Abhijit; Prakash, Avinash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This case report delves into the diagnostic challenges faced when differentiating between sepsis and dengue shock syndrome (DSS), particularly in regions where both are endemic. A 23-year-old female initially diagnosed with DSS presented with fever, thrombocytopenia, and multi-organ dysfunction. Despite aggressive DSS management, the patient's condition worsened, prompting further investigation. Blood cultures eventually revealed Klebsiella pneumoniae, leading to a shift in diagnosis to sepsis. This case underscores the importance of comprehensive diagnostic evaluation, which included blood cultures, serological tests, and imaging. Prompt initiation of targeted antibiotics and comprehensive critical care resulted in significant improvement, highlighting the critical role of early recognition and intervention in optimizing outcomes. The complexities in distinguishing between sepsis and DSS underscore the need for continuous vigilance and a thorough diagnostic approach in similar clinical scenarios.